2004
DOI: 10.1016/j.intcom.2003.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of religious affiliation on trust in the context of electronic commerce

Abstract: There is currently a growing literature on the role that trust plays in encouraging consumers to engage in e-commerce transactions. Various models have been proposed which aim to identify both the antecedents and outcomes of trust displayed towards e-commerce web sites.Increased trust is generally shown to increase positive user attitude which in turn is linked to increased willingness to buy. Studies have shown the antecedents of trust include variables such as the perceived reputation and size of the vendor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 30 publications
1
22
1
Order By: Relevance
“…People may be separating evaluation of usability and aesthetics from identity and treating them objectively. Respondents favored matching identity websites and evaluated them more favorably than websites from other religions (both Muslims and Christians); which partially agrees with Siala et al [8] results that only Muslims trusted matching identity websites while Christians favored neutral websites. Brand affected respondents' judgment of content, service quality, usability and aesthetics which agrees with De Angeli et al [4] who demonstrated that people who have positive attitudes towards the website brand were more positive in the evaluation of aesthetics, pleasure and usability.…”
Section: Discussionsupporting
confidence: 85%
“…People may be separating evaluation of usability and aesthetics from identity and treating them objectively. Respondents favored matching identity websites and evaluated them more favorably than websites from other religions (both Muslims and Christians); which partially agrees with Siala et al [8] results that only Muslims trusted matching identity websites while Christians favored neutral websites. Brand affected respondents' judgment of content, service quality, usability and aesthetics which agrees with De Angeli et al [4] who demonstrated that people who have positive attitudes towards the website brand were more positive in the evaluation of aesthetics, pleasure and usability.…”
Section: Discussionsupporting
confidence: 85%
“…This finding has been also shown to impact the center of attention on a screen, suggesting that error messages and important interface elements should be placed according to the start location of a person's writing system orientation (Röse 2005). Another cultural influence is religion, which is often named as a mediator of preferences for certain symbols and colors, and implicitly the feeling of trust (Siala et al 2004). Furthermore, varying education levels contribute to the creation of cultural groups, so-called "subcultures" (Karahanna et al 2005).…”
Section: Cultural Influences On Ui Perception and Preferencesmentioning
confidence: 99%
“…In addition, there are many aspects of culture that have been found to impact interface preferences, such as a user's first (and second) language [Nisbett 2003;Röse 2005], religion [Siala et al 2004], the education level and the form of education. For example, people who have mostly received teacher-centered instruction are more likely to appreciate detailed instructions later in life [Reinecke 2005], and this seems to be a decisive factor for the self-determined handling of computers.…”
Section: Culture and Its Influences On Human-computer Interactionmentioning
confidence: 99%